Dissecting super-enhancer hierarchy based on chromatin interactions - Jialiang Huang (Nature Portfolio, 2018)
Super-enhancers (SEs) are important regulatory elements for gene expression, but their intrinsic properties remain poorly understood. Here the authors analyse Hi-C and ChIP-seq data and find that a significant fraction of SEs are hierarchically organized, containing both hub and non-hub enhancers.